A 56‐year‐old female with celiac artery compression syndrome recovering through dietary changes and weight gain. (2nd May 2017) - Yoshida, Kiichiro; Kita, Keiichiro; Yamashiro, Seiji
Abstract: Celiac artery compression syndrome is a rare condition characterized by extrinsic compression of the celiac artery by the median arcuate ligament, which leads to chronic, recurrent postprandial epigastric pain. Although traditional treatment of this syndrome involves laparotomy to release the median arcuate ligament, here we report on the rare case of a middle‐aged woman recovering with no specific treatment through her use of a food diary to change her diet which resulted in gradual weight gain. This suggests that in some cases, a conservative therapy for celiac artery compression syndrome should be tried before choosing surgical intervention.